Sinus venosus atrial septal defect and partial anomalous pulmonary venous connection in a patient with dextrocardia. Issue 2 (28th February 2022) - Shimajiri, Hiroto; Harada, Yu; Kinoshita, Mirai; Mikami, Shinsuke
Abstract : An 85-year-old woman presenting with symptomatic pulmonary hypertension (PH) with a history of dextrocardia was referred to our facility for treatment of heart failure. Significant shunting was detected by measuring oxygen saturation during right heart catheterisation (RHC). CT with contrast revealed sinus venosus atrial septal defect (SVASD) and partial anomalous pulmonary venous connection (PAPVC), in which the left upper and middle lobar pulmonary veins returned to the superior vena cava and right atrium. Despite medical treatment, the patient died, and an autopsy was performed. SVASD and PAPVC are rare congenital anomalies. RHC with measurement of oxygen saturation and CT with contrast should be considered in patients with unexplained right atrial and ventricular enlargement or suspected PH.